MENINGKATKAN PEMAHAMAN KONSEP NILAI TEMPAT BILANGAN MELALUI MEDIA BLOK DIENES PADA ANAK TUNAGRAHITA RINGAN DI KELAS D IV C SDLBN TALAWI KOTA SAWAHLUNTO - Syafris - Novembris (Universitas Negeri Padang, 2012)
The background of this research is where the D class IV C Tunagrahita have difficulty in understanding the place value of numbers, so far the work done in membelajarkan child's teacher using the abacus and the media stick, but apparently the media has not brought the business of teachers expected results. The purpose of this study is to improve the ability to understand the place value of numbers through the media block dienes in class IV C D SLBN Talawi Sawahlunto. This is due to the medium used has not been able to increase the capability of understanding the concept of place value of numbers of children light Tunagrahita This study aims to determine how to improve teachers' understanding of the concept of place value of numbers in children Tunagrahita light. This research methodology was action research class (classroom action research) is done in the form of collaboration. This action is done to the two children who had been the subject of research, namely child lightweight Tunagrahita D class IV C SLBN Talawi Sawahlunto.